Implementation of the Occupational Safety and Health Management System to the Daily Activities of Employees and Visitor Reception at PT X - Muh. Rifqi Aditya Harliman; Bugi Nugraha; Akhmad Kasan Gupron; Faris Nofandi (Journal of Engineering Science and Technology Management (JES-TM), 2026)
Occupational Safety and Health (OSH) management in Liquified Natural Gas (LNG) terminals requires stringent alignment with both general workplace safety and process safety protocols. This study evaluates the implementation of the OSH Management System (SMK3) at PT X, an LNG logistics terminal in Indonesia, focusing on employee Personal Protective Equipment (PPE) compliance and visitor safety controls. Utilizing a qualitative case study design, data were collected through field observations, document reviews, and semi-structured interviews with nine key informants across operational and safety divisions. The data were analyzed using a formal SWOT/TOWS matrix to develop strategic interventions. The findings indicate that while PT X’s institutional procedures—such as mandatory safety inductions, daily toolbox meetings, and medical fit-to-work screenings—are consistent with ISO 45001 standards, critical field execution gaps remain. Empirical evidence highlights recurring PPE non-compliance driven by human factors (e.g., thermal discomfort), visitor violations of electronic device restrictions in hazardous explosive zones, and logistical bottlenecks due to insufficient visitor PPE inventory during peak periods. The study concludes that achieving optimal safety compliance requires moving beyond bureaucratic procedures. Practical implications include the necessity for risk-based PPE procurement, the enforcement of a controlled intrinsically-safe device management policy, and enhanced human-centric safety supervision.